Fourteen‐Year Acceleration Along the Japan Trench. Issue 11 (28th October 2021) - Marill, Lou; Marsan, David; Socquet, Anne; Radiguet, Mathilde; Cotte, Nathalie; Rousset, Baptiste
Abstract: An acceleration of the background seismicity and a shortening of the slow slip events recurrence intervals in the Boso peninsula (Japan) suggest a slow unlocking of the Philippine Sea‐North America (PHS‐NAM) subduction interface from 1990 to 2011. Motivated by these previous observations, we used GPS (Global Positioning System) time series to study the 1997–2011 evolution of interface locking offshore Honshu with a specific focus on the Kanto region. We newly processed the GPS data in double difference and analyzed them with a trajectory model that accounts for seismic and aseismic variations, and that includes an inter‐seismic acceleration term. We inverted the surface acceleration obtained, on both the Pacific‐North America (PAC‐NAM) and the PHS‐NAM interfaces. The inverted slip rate changes over time compare well with previous studies: we infer slip deceleration between 39 ° – 41 ° N and acceleration between 37 ° – 38 ° N (PAC‐NAM), with a maximum amplitude of 1.75 mm/ y r 2 corresponding to an equivalent geodetic locking change of 0.3 over the 14 years. More notably, our analysis reveals a novel and robust slip acceleration South of 36 ° N that we interpret as an unlocking of the PAC‐NAM interface. It is located noticeably far from the 2011 Tohoku earthquake rupture and is therefore unlikely connected to it. The slip acceleration inverted from the surface displacements is comparable to the changes observed in the seismicity rate. Our results further demonstrate that inter‐seismic slip rate can significantly evolve over years to decades, and suggest a simple relationship between the seismicity and the slip on the subduction interface. Plain Language Summary: Subduction zones, where an oceanic plate dives under a continental plate, host both seismic and aseismic slip events. In Japan, along the Sagami Trough where the Philippine Sea (PHS) plate subducts beneath the North America (NAM) plate, the increase of the number of earthquakes between 1990 and 2011 suggests that the PHS plate slips at a higher rate under the NAM plate. Along the Japan Trench, North of the Sagami Trough, the Pacific (PAC) plate subducts beneath the NAM plate; changes in the slip rate of the PAC plate have already been inferred from geodetic measurements by previous studies. To further investigate those changes in slip rate at both interfaces, we processed and analyzed GPS (Global Positioning System) time series from 1997 to 2011, and compared them with changes in earthquake rates. From those time series, we determine the slip rate of the continental plate. On the PAC‐NAM interface, the slip either decelerates or accelerates depending on the location. Most notably, our analysis reveals a novel slip acceleration near the Boso peninsula that we interpret as an acceleration of the PAC plate's slip beneath the NAM plate, proving that plates can subduct at non‐stationary velocities. Key Points: We reveal a novel and robust acceleration of the surface displacement in the Kanto area over 1997–2011 We infer a slip rate acceleration along the Pacific‐North America subduction interface, both offshore Kanto and Tohoku regions We propose a simple relationship that relates the observations with changes in seismicity and slip rates